Technical Analysis and Development of Single Bamboo Floating from the Perspective of Education and Psychology - Youji Wang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Surprisingly, solo bamboo drifting, which originated from indigenous boating in southwestern China, has evolved into a new and captivating sport. This research focuses on the competitive aspect of solo bamboo drifting, examining the oar-rowing strategies and techniques through which top athletes achieve success. The study aims to provide evidence-based training advice for participants by analysing the performance of five athletes selected based on their results in a 60-meter straight track event. Research methods include literature review, observation, video analysis, and statistical mathematics. The Dartfish sports technique video analysis system is employed to scrutinize precise movements and compare them to evaluate pole-rowing techniques. Findings indicate that athletes' positioning on the bamboo, the angle of pole entry into the water, rowing power and speed management, and bamboo direction control are crucial technical aspects affecting competitive outcomes. Correct posture and efficient pole-rowing techniques minimize water drag and enhance bamboo velocity. Effective force management ensures bamboo stability and rowing efficiency. Yawing phenomena during competition disrupt rowing rhythm and stability, hindering performance. The study conducts a comparative analysis of the pole-rowing tactics of three athletes, identifying differences in movement intricacies and effectiveness throughout the rowing cycle. The findings provide a scientific foundation for future training, offering specific recommendations such as using advanced technology for technical monitoring, enhancing physical training for better rowing efficiency, and practicing direction control under various conditions. These guidelines aim to help athletes optimize their techniques and improve competition performance. This research not only provides theoretical support for technical training in solo bamboo drifting but also offers practical instructions for the sport's scientific advancement and broader adoption.